Multiplexed Massively Parallel Sequencing of Plastomes Provides Insights Into the Genetic Diversity, Population Structure, and Phylogeography of Wild and Cultivated Coptis chinensis - Wang, Yiheng; Sun, Jiahui; Zhao, Zhenyu; Xu, Chao; Qiao, Ping; Wang, Sheng; Wang, Mengli; Xu, Zegang; Yuan, Qingjun; Guo, Lanping; Huang, Luqi (Frontiers in Plant Science, 2022)
Root rot has been a major problem for cultivated populations of Coptis chinensis var. chinensis in recent years. C. chinensis var. brevisepala, the closest wild relative of C. chinensis var. chinensis, has a scattered distribution across southwestern China and is an important wild resource. Genetic diversity is associated with greater evolutionary potential and resilience of species or populations and is important for the breeding and conservation of species. Here, we conducted multiplexed massively parallel sequencing of the plastomes of 227 accessions of wild and cultivated C. chinensis using 111 marker pairs to study patterns of genetic diversity, population structure, and phylogeography among wild and cultivated C. chinensis populations. Wild and cultivated resources diverged approximately 2.83 Mya. The cultivated resources experienced a severe genetic bottleneck and possess highly mixed germplasm. However, high genetic diversity has been retained in the wild resources, and subpopulations in different locations differed in genotype composition. The significant divergence in the genetic diversity of wild and cultivated resources indicates that they require different conservation strategies. Wild resources require in situ conservation strategies aiming to expand population sizes while maintaining levels of genetic diversity; by contrast, germplasm resource nurseries with genotypes of cultivated resources and planned distribution measures are needed for the conservation of cultivated resources to prevent cultivated populations from undergoing severe genetic bottlenecks. The results of this study provide comprehensive insights into the genetic diversity, population structure, and phylogeography of C. chinensis and will facilitate future breeding and conservation efforts.